2013
DOI: 10.1590/s1806-83242013005000002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mechanical properties of five cements for orthodontic band cementation

Abstract: The aim of this in vitro study was to compare the flexural, compressive and diametral tensile strengths of five cements used in orthodontics for band cementation. MPa, 137.41 MPa, and 20.50 MPa. The statistical analysis was performed by two-way ANOVA and Tukey tests with p-value ≤ 0.05. In terms of diametral tensile strength, BL showed the highest strength statistically, and MC, the second highest. In terms of compressive tensile strength, BL showed the highest strength statistically, and FJ did not attain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Regarding CS, previous studies found similar values to those observed in conventional and RMGI cements analyzed in our study [ 41 , 42 , 43 , 44 ]. On the other hand, in this study the experimental groups with 5% and 10% of Halloysite nanotubes preloaded with chlorhexidine showed an increase in CS, which can be considered a positive modification.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding CS, previous studies found similar values to those observed in conventional and RMGI cements analyzed in our study [ 41 , 42 , 43 , 44 ]. On the other hand, in this study the experimental groups with 5% and 10% of Halloysite nanotubes preloaded with chlorhexidine showed an increase in CS, which can be considered a positive modification.…”
Section: Discussionsupporting
confidence: 89%